The response to the DNA damaging agent methyl methanesulfonate in a fungal plant pathogen. Issue 5 (May 2019) - Milo-Cochavi, Shira; Pareek, Manish; Delulio, Gregory; Almog, Yael; Anand, Gautam; Ma, Li-Jun; Covo, Shay
Abstract: DNA damage can cause mutations that in fungal plant pathogens lead to hypervirulence and resistance to pesticides. Almost nothing is known about the response of these fungi to DNA damage. We performed transcriptomic and phosphoproteomic analyses of Fusarium oxysporum exposed to methyl methanesulfonate (MMS). At the RNA level we observe massive induction of DNA repair pathways including the global genome nucleotide excision. Cul3, Cul4, several Ubiquitin-like ligases and components of the proteasome are significantly induced. In agreement, we observed drug synergism between a proteasome inhibitor and MMS. While our data suggest that Yap1 and Xbp1 networks are similarly activated in response to damage in yeast and F. oxysporum we were able to observe modules that were MMS-responsive in F. oxysporum and not in yeast. These include transcription/splicing modules that are upregulated and respiration that is down-regulated. In agreement, MMS treated cells are much more sensitive to a respiration inhibitor. At the phosphoproteomic level, Adenylate cyclase, which generates cAMP, is phosphorylated in response to MMS and forms a network of phosphorylated proteins that include cell cycle regulators and several MAPKs. Our analysis provides a starting point in understanding how genomic changes in response to DNA damage occur in Fusarium species.